Self and body in early East Asian thought - Lewis, Mark Edward 1954- (Cambridge University Press, 2024)
This Element examines evolving methods of cultivating the embodied self, including healing diseases and creating a superior person, in late Warring States and early imperial East Asia. It analyses many topics, including the textualization of bodily regimens and therapies, their systematization, their dissemination among different (and sometimes rival) social groups, and the diversity of traditions - religious, pharmacological, nourishing of life - that contested and combined to form a hegemonic medical practice. These topics in turn feature several issues: models of the body, regimens of cultivating and extending vitality, models of disease, and therapies for these ailments. All these ideas will be refined and extended through comparison with early Western medical traditions
Title from publisher's bibliographic system (viewed on 24 Jan 2025)
Keywords: Alternative medicine / East Asia / History; Holistic medicine / East Asia / History; Self (Philosophy) / East Asia / History; Mind and body / East Asia / History